The so-called eighth Stromateus by Clement of Alexandria: early Christian reception of Greek scientific methodology - Havrda, Matyáš (Philosophia antiqua, 2017)
The so-called eighth Stromateus ('liber logicus') by Clement of Alexandria (d. before 221 C.E.) is an understudied source for ancient philosophy, particularly the tradition of the Aristotelian methodology of science, scepticism, and the theories of causation. A series of capitula dealing with inquiry and demonstration, it bears but few traces of Christian interests. In this volume, Matyáš Havrda provides a new edition, translation, and lemmatic commentary of the text. The vexing question of the origin of this material and its place within Clement's oeuvre is also addressed. Defending the view of 'liber logicus' as a collection of excerpts made or adopted by Clement for his own (apologetic and exegetical) use, Havrda argues that its source could be Galen's lost treatise On Demonstration